Editorial board, information for authors, and other front matter - Ricky Telg (Journal of Applied Communications, 2012)
This content includes the front cover, the table of contents, editorial and other information for authors for vol. 96, no. 3 (2012) of Journal of Applied Communications
Keywords: masthead